2013
DOI: 10.1021/la403379g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Oxygen Atom of the Hydrophobic Chain on the Self-Assembly Property and Morphology of the Pyridyl Boronic Acid Based Amphiphiles

Abstract: The surface activity and aggregation behavior of two synthesized boronic acid based anionic surfactants, sodium salt of 2-dodecyl pyridine-5-boronic acid (SDDPB) and sodium salt of 2-oxydodecyl pyridine-5-boronic acid (SODDPB), were studied in buffer solution at pH 9 and 13 containing carbohydrates. The self-assembly formation was investigated by use of a number of techniques including surface tension, conductivity, fluorescence spectroscopy, dynamic light scattering, X-ray diffraction, and transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Figure d shows the image of the middle phase of the AS3P of the C 14 ‐MPA‐Na (31 m m )/CTAB system. Interestingly, network structures are formed in this middle phase, and the meshes distributed in the micelles have various sizes, which demonstrates that sponge‐like micelles are formed . Figure e shows the image of the lower phase of the AS3P of the C 14 ‐MPA‐Na (31 m m )/CTAB system.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure d shows the image of the middle phase of the AS3P of the C 14 ‐MPA‐Na (31 m m )/CTAB system. Interestingly, network structures are formed in this middle phase, and the meshes distributed in the micelles have various sizes, which demonstrates that sponge‐like micelles are formed . Figure e shows the image of the lower phase of the AS3P of the C 14 ‐MPA‐Na (31 m m )/CTAB system.…”
Section: Resultsmentioning
confidence: 94%
“…Interestingly,n etwork structures are formed in this middle phase, and the meshes distributed in the micelles have various sizes, which demonstrates that sponge-like micelles are formed. [48][49][50] Fig-ure 7e shows the image of the lower phase of the AS3P of the C 14 -MPA-Na (31 mm)/CTAB system. The micelles in this solution are similar to those in the lower phase of the ASTP,t hat is, they are spherical and rod-like micelles.T he Cryo-TEMi mage of the anisotropic homogeneous phase of the C 14 -MPA-Na (35 mm)/CTAB system shown in Figure 7f also reveals sponge-like micelles.…”
Section: Cyro-temmentioning
confidence: 99%
“…As the fructose is strongly binding carbohydrate of boronic acid, different amount of fructose (0.02‐0.5 M) was tested to solubilize the amphiphile at higher pHs and it was found that 0.5 M fructose was required to make the aggregate solution stable. The details of selecting proper solvent was given in our earlier publication . The pK a value of the amphiphiles were determined by steady state fluorescence anisotropy ( r ) measurements using DPH probe at buffer solutions of different pHs having 0.5 M fructose and at fixed concentration of the amphiphiles.…”
Section: Resultsmentioning
confidence: 99%
“…All reactions were monitored by thin-layer chromatography on silica gel GF254 pre-coated plates (0.25 mm). The Grignard reagents n -C 11 H 23 MgBr, n -C 13 H 27 MgBr and n -C 15 H 31 MgBr were prepared according to a reported method from the corresponding n -alkyl bromide [ 43 ]. 1 H and 13 C NMR spectra were recorded on Varian Inova—400 MHz spectrometers using tetramethylsilane as the internal standard, and were reported in terms of chemical shift (δ ppm).…”
Section: Methodsmentioning
confidence: 99%